Environmental effects on star formation main sequence in the COSMOS field. Issue Volume 15:Issue S356(2019) (October 2019) - Randriamampandry, Solohery M.; Vaccari, Mattia; Hess, Kelley M.
Abstract: We investigate the relationship between environment and star formation main sequence (the relationship between stellar mass and star formation rate) to shed new light on the effects of the environments on star-forming galaxies. We use the large VLA-COSMOS 3 GHz catalogue that consist of star-forming galaxies (SFGs) and active galactic nuclei (AGN) in three different environments (field, filament, cluster) and for different galaxy types. We examine for the first time a comparative analysis for the distribution of SFGs with respect to the star formation main sequence (MS) consensus region from the literature, taking into account galaxy environment and using radio selected sample at 0.1 ≤ z ≤ 1.2 drawn from one of the deepest COSMOS radio surveys. We find that, as observed previously, SFRs increase with redshift independent on the environments. Furthermore, we observe that SFRs versus M* relation is flat in all cases, irrespective of the redshift and environments.